Factors that affect the value of a company with profitability as moderation - Arthur Mukuan; Tutty Nuryati; Tri Yulaeli; Betty Nurbaiti; Endah Puspaningrum (Research Trend in Technology and Management, 2025)
This study aims to look at the influence of managerial ownership and audit committees on the value of the Company with profitability as a moderation variable. This research uses Software Eviews 12. The analysis methods used were panel data regression test, thirst test, langarange multiplier test, determination coefficient test (adjuster R2), and hypothesis test. This study aims to formulate a hypothesis that will guide future research in this field. In compiling this literature review article, the approach used is the library research method, with sources obtained from online platforms such as Google Scholar, Mendeley, and various other academic databases. The results of this literature review highlight the influence of managerial ownership and audit committees on company value, with profitability acting as a moderation variable. The results of this study show that managerial ownership has no effect on the Company's value, the audit committee has a negative effect on the Company's value, and profitability is not able to moderate managerial ownership and the audit committee on the company's value.